PEMIKIRAN SYAUQI DHAIF DAN UPAYA PEMBAHARUANNYA DI BIDANG PENGAJARAN NAHWU (Telaah Buku Tajdid al-Nahwi Karya Syauqi Dhaif) - Ardinal, Eva (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Science of Nahwu is recognized as a discipline that is loaded with a variety of rules and theories, as the result of a process of a long journey in the history of Arabic linguistics. Starting from the codification and systemization activities of Arabic vocabulary is quite time consuming, then linguists (al-Lughawiyyûn / linguist) construct and lay the basic principles of the rules of the language. The basic principles of nahwu at first is very simple then evolved into a "science" which is very complicated and cumbersome. Nahwu is no longer just functions as a deductive rule or a grammar, but it also has become one of the instruments to understand the Quran itself, which in turn gave rise to many theories nahwu developed by experts nahwu (nuhât / Grammarian). This, of course, more difficult to understand and learn the science of Nahwu itself. For the purposes of education and teaching that is deemed necessary rethinking and renewal (tajdid) in the field of teaching and teaching nahwa materials simplification.